Ordnungsdefizite in Marktwirtschaften: 50 Jahre Forschungsseminar Radein - Thieme, Hans Jörg (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The communication brings the summary and background of discussion carried out in this year Radino seminar (Italy – South Tirol). This is a traditional summit of German economists dealing with economic system, where they carry out presentations and discussions on differences between system of central planning and market system. They are using examples from history: Soviet Union, Yugoslavia and modern market economies as well as European transition countries. Interested reader will get the opportunity to deepen her or his knowledge on elements that can be recognized in today’s populist politics – from cutting trade links up to proposed state intervention in order to carry our redistribution of income. The author also discusses positions of top representatives of the German historical school and social – market economy.